PERANAN ROOM ATTENDANT DALAM MENINGKATKAN STANDARD KUALITAS LAYANAN KEBERSIHAN KAMAR DI CK TANJUNGPINANG HOTEL & CONVENTION CENTRE - Muhammad Nur Saiful Hidayat; Harnisa Octaviani (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2025)
This research was conducted because there were Standard Operating Procedures that had not been implemented optimally. The purpose of this research was to find out and analyze the application of Standard Operating Procedures (SOP), how room attendants work in implementing standard operating procedures in an effort to improve the quality of room cleaning services at CK Tanjungpinang Hotel & Convention Centre. This study uses a descriptive qualitative method which describes the application of Standard Operating Procedures for Room Attendants at CK Tanjungpinang Hotel & Convention Center. The data collection used is direct observation, interviews, and literature studies that support this research. The results of this study are that Standard Operating Procedures (SOP) have been implemented, but the implementation is not optimal, so there is a need for training and monitoring at all times so that the quality of room cleanliness is maximized.